Institutions and entrepreneurship - Sine, Wesley D.; David, Robert J. (Research in the sociology of work, 2010)
In this volume, we examine how the institutional environment affects entrepreneurial organizations, and vice-versa. This includes not only how the institutional environment constrains both founding processes and the type of organizations founded, but also how institutional dynamics construct new entrepreneurial opportunities, empower and facilitate action, and how entrepreneurs manipulate the institutional environment to serve their own ends. This institutional approach to entrepreneurship shifts attention away from the personal traits and backgrounds of individual entrepreneurs, and towards how institutions shape entrepreneurial opportunities and actions; how entrepreneurs navigate their cognitive, normative, and regulatory environments; and how actors modify and build institutions to support new types of organizations.